The 8th Work of Mercy "To care for our common home": Initial exploration of the contribution of food gardening within and by Christian communities in the Quest for Sustainable Food Justice - Stichel, Ellen Van (International journal for the study of the Christian church, 2023)
In 2016, Pope Francis complemented the seven works of mercy, including "feeding the hungry" with an eighth one, following his encyclical Laudato si': "Let us be merciful to our common home." While ending hunger is an SDG-goal, the impact of climate change makes it abundantly clear the need for sustainable food justice. Across the globe, projects are emerging to implement this food justice. As an illustration, we could refer to the increasing interest in forest/food gardening. Although no credit is due to Christianity, in the Low Countries we notice how monasteries and abbeys explicitly subscribe to this trend. In this contribution, I want to link such initiatives to Catholic social thought, focusing on its implications for the discussion on the distinction between charity and justice on the one hand, and the notion of "integral ecology" on the other, and how individual Christians and communities can play a prophetic role.